Pemanfaatan Visualisasi Data dalam Business Intelligence untuk Strategi Bisnis Perusahaan Retail - Sasha Safira Nuraini; Azzumardi Mubarok Romadhoni; Muhammad Akmal Faris Taqiyuddin; Ma’had Wicaksono (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study investigates how data visualization helps retail companies make Business Intelligence (BI)-based decisions. The study processed one year of sales data with a quantitative descriptive approach to find seasonal patterns, performance by region, and customer consumption tendencies. The analysis results show that BI software such as Microsoft Power BI can visualize data more easily and accelerate understanding of business performance. Strategic decisions such as promotional planning and product inventory management are more effective with interactive visualization, which allows decision makers to see data in a more understandable way. The study found that data visualization in BI systems can help retail businesses make better decisions. These results show the importance of incorporating BI into a company's operational processes and using interactive visualization to improve overall business performance.